Effects on visual basic programming instructional delivery using web-based tools for students’ interest and academic achievement in universities, Nigeria - Onah, Benardine Ifeoma; Eze, Blessing Ngozi; Uzoegwu, Chigozie Roseann; Chiamagu, Charles; Mgboji, Chukwuma; Ugwuanyi, Christian Sunday (Education and information technologies, 2024)
This research work ascertained the effect of Visual Basic (VBasic) Programming Instructional Delivery using Web-Based Tools on Students’ Interest and Academic Achievement in Universities in Nigeria. The purpose of the study is to determine the effect of Visual Basic (VBasic) Programming Instructional Delivery using Web-Based Tools on Students’ Interest and Academic Achievement in Universities in Nigeria. The study embraced a quasi-experimental research design. The respondent for this study comprised 74 students in year two of Alex Ekwueme Federal University, Ndu-ufu Alike and Ebonyi State University, Abakaliki. For the fact that the population is small and manageable, the entire population were studied. Researchers used VBasic Programming Achievement Test (VBPAT) instrument developed to collect data. Visual Basic Achievement Test contained 50-item questions with letter A to D options for each interest scale were used for data collection. The reliability was tested using Cronbach’s Alpha. To ensure consistency and integrity, lecturers in the study area. The researchers trained the lecturers on how to distribute the instrument for both the experiment and control groups in order to ensure homogeneous instruction. The lecturers taught the experimental group using the utilization of a web-based approach and the control group using the conventional approach. Scores generated from the experimental test using Visual Basic programming Achievement Test (V + B + PAT), were analysed using mean and analysis of covariance (ANCOVA) for answering research questions and to test hypotheses respectively at 0.5 level of significance with the aid of statistical package for social science (SPSS) version 20. The outcome of this study on research question on influence of location on the students’ academic achievement mean gain in Vbasic programming language when taught using web-based tool, showed that with the use of web-based tool in the instructional delivery of VBasic programming language brought about better improvement in students’ academic achievement. Furthermore, the outcomes of hypothesis tested showed that location is significant source of different in mean achievement scores for students taught with Visual Basic Programming language using web-based approach and visual basic programming using conventional approach. This study has implications for facilitators, learners, curriculum planners, ministries in Education among others. This study found out among others that the facilitators use web-based tools in distance education for quiz, assessment, examinations, and instructional delivery of Vbasic programming language to a less extent in Nigerian Universities. It was concluded therefore, that conventional method is less effective than web-based approach in improving student’s achievement in Visual Basic Programming. Hence Nigerian Universities should adopt the use of web-based approach in computer programming lecturers.